EDITORIAL | REDAKTORIAUS ŽODIS - Çelik, Servet (Sustainable Multilingualism / Darnioji daugiakalbystė, 2023)
This issue trails the 5th International Conference “Sustainable Multilingualism 2019,” organized by the Institute of Foreign Languages of Vytautas Magnus University, Lithuania, in cooperation with the Language Teachers’ Association of Lithuania in Kaunas, Lithuania, on May 24–25, 2019. The conference brought together hundreds of scholars from a wide range of disciplines including language education, linguistics, psychology, philosophy, literature and medicine, and many language professionals and enthusiasts worldwide, and was a huge success. I congratulate my good friend and colleague Prof. Nemira Mačianskienė of Vytautas Magnus University Institute of Foreign Languages, the editor-in-chief of our journal and chair of the conference since 2011, and her conference team, for the meticulous planning in setting up such a well-coordinated event.